Heterogenous Late Holocene Climate in the Eastern Mediterranean—The Kocain Cave Record From SW Turkey. Issue 20 (18th October 2021) - Jacobson, Matthew J.; Flohr, Pascal; Gascoigne, Alison; Leng, Melanie J.; Sadekov, Aleksey; Cheng, Hai; Edwards, R. Lawrence; Tüysüz, Okan; Fleitmann, Dominik
Abstract: Palaeoclimate variability must be constrained to predict the nature and impacts of future climate change in the Eastern Mediterranean. Here, we present a late Holocene high‐resolution multiproxy data set from Kocain Cave, the first of its kind from SW Turkey. Regional fluctuations in effective‐moisture are recorded by variations in magnesium, strontium, phosphorous and carbon isotopes, with oxygen isotopes reacting to changes in precipitation and effective‐moisture. The new record shows a double‐peak of arid conditions at 1150 and 800 BCE, a wet period 330–460 CE followed by a rapid shift to dry conditions 460–830 CE, and a dry/wet Medieval Climate Anomaly/Little Ice Age pattern. Large discrepancies exist between Turkish records and the Kocain record, which shares more similarities with other Eastern Mediterranean coastal records. Heterogeneity of regional climate and palaeoclimate proxy records are emphasized. Plain Language Summary: Records of past climate are essential in the Eastern Mediterranean to understand regional impacts of modern climate change. In combination with archeology, these allow us to examine climatic impacts on people in the past to help us prepare for the future. Here, we examine a stalagmite (Ko‐1) from Kocain Cave, southwest Turkey, which contains information about past climate change in its chemistry. Measurements of trace‐metals and carbon isotope ratios record the amount of water entering the cave, oxygen isotope ratios record rainfall amount. Measurements of uranium are used to date the climate changes. Earthquakes that damaged nearby cities and caused tsunamis changed the angle of the stalagmite, providing more evidence for dating the sample. The Kocain Cave record shows climatic conditions changed frequently in southwest Turkey. Important are dry conditions 1150 and 800 BCE, wet conditions 330–460 CE followed by a rapid shift to dry conditions 460–830 CE, and a dry/wet Medieval Climate Anomaly/Little Ice Age pattern. These climate changes were different to records from elsewhere in Turkey and matched better with coastal records from Greece and Lebanon/Israel. The complex nature of past climate is emphasized due to varied climatic regions in Turkey and the many impacts on each record. Key Points: Stalagmite Ko‐1 record of effective‐moisture from SW Turkey stresses spatial and temporal heterogeneity of Turkish climate Climate changes share more similarities with other Eastern Mediterranean coastal regions, than central or northern Turkey Heterogeneity of modern climate and proxy records highlight the complexity of historical comparisons